Development of Starch Nanoparticle from Mango Kernel in Comparison with Cereal, Tuber, and Legume Starch Nanoparticles: Characterization and Cytotoxicity. (14th January 2022) - Nain, Vikash; Kaur, Maninder; Sandhu, Kawaljit Singh; Thory, Rahul; Sinhmar, Archana
Abstract: Starch nanoparticles (SNPs) are developed from mango kernel starch and are compared with wheat, potato, mungbean, and water chestnut starch nanoparticles. The synthesized SNPs are investigated for their thermal properties, particle size, degree of relative crystallinity and cytotoxicity. The average particle size of SNPs from different botanical sources range from 100 to 514 nm. Mango kernel starch nanoparticles show the highest particle size. Starch nanoparticles from all botanical sources show X‐ray diffraction (XRD) patterns similar to their native counterpart starches. SNPs from wheat, mango kernel, and water chestnut show A‐type XRD patterns but the relative crystallinity of SNPs is observed to be higher as compared to native starches. From the thermogravimetric analysis, it is observed that degradation temperature for 10% loss weight vary significantly. The study reveals that mango kernel SNPs show good biocompatibility with human HeLa cell lines as compared to all other sources except water chestnut SNPs. Abstract : Starch nanoparticles are synthesized from mango kernel and their various properties such as particle size, cytotoxicity, etc. are compared with cereal, tuber, and legume starch nanoparticles. The results reflect that botanical sources greatly affect various properties of starch nanoparticles.